Markkinarenkuttimesta Martin Pauliin : harmonikka kansanvalistuksen ja populaarimusiikin Suomessa 1850–1900 - Lepistö, Markku (Taideyliopiston Sibelius-Akatemia, 2016)
This thesis forms part of my D.Mus. degree at the Sibelius Academy of the University of the Arts Helsinki. My artistic project focused on performing historical popular music and writing new music for bisonoric diatonic accordions. In this written thesis, I explore the early history of the accordion in the Grand Duchy of Finland in the latter half of the 19th century. The artistic project of my doctorate comprised the concerts Salongista tupaan (From salon to cottage, 2011), New Melodeon Melodies (2013), Organetto Solo (2014), Palkein ja kielin – ääniä maisemassa (Bel- lows and reeds – sounds in the landscape, 2014) and Organetto & Organo (2016). The purpose of the artistic project for the single-row accordion was to unearth historical popular music that was actually performed on the accordion in the 19th century and to write original pieces of new folk music for the instrument. For the larger, 2.5-row and three-row bisonoric accordions, the purpose was principally to write original music while developing my musical idiom and palette of expression. Some of the music I wrote was firmly rooted in the instrumental characteristics of bisonoric accordions, but on the other hand I also considered it important to create music that would transcend instrumental and genre borders. In the written thesis, I focused specifically on early sales channels for accordions, early performers on the accordion and aspects of public appreciation of the instrument. My principal source database was the digi- tal newspaper archive maintained by the Finnish National Library, where I could search for and compile a wealth of information about instrument sellers, instrument repairers and accordion builders, among other things. I also discuss the debate on the accordion at the height of the folk education movement. A key figure in this debate was the German-Danish-Finnish accordionist Martin Paul (1843-1893), who created a significant career as a performing artist and an accordion teacher in Finland between 1879 and 1893.

Tämä kirjallinen työ on osa musiikin tohtorintutkintoani Taideyliopiston Sibelius-Akatemiassa. Taiteelli- sen työni aiheena oli sekä historiallisen populaarimusiikin esittäminen että uuden harmonikkamusiikin säveltäminen vaihtoäänisille diatonisille pikkuharmonikoille. Kirjallisessa työssäni olen selvittänyt harmonikan varhaishistoriaa Suomen suuriruhtinaskunnassa 1800-luvun jälkipuoliskolla. Tohtorintutkinnon taiteellisen kokonaisuuden muodostivat konsertit Salongista tupaan (2011), New Melo- deon Melodies (2013), Organetto Solo (2014), Palkein ja kielin – ääniä maisemassa (2014) ja Organetto & Organo (2016). Taiteellisessa työssäni päämääränä yksirivisen harmonikan kohdalla oli tuoda esiin sekä historiallista, 1800-luvulla harmonikalla esitettyä populaarimusiikkia että säveltää sille uutta nykykansanmusiikkia. Isompien 2,5- ja 3-rivisten vaihtoäänisten harmonikkojen kohdalla päämääränäni oli säveltää ennen kaikkea uutta musiikkia ja samalla kehittää ja monipuolistaa omaa sävelkieltä ja ilmaisukeinoja. Osa sävellystyöstäni lähti selkeästi vaihtoäänisten harmonikkojen soittimellisuudesta, mutta toisaalta pidin tärkeänä luoda musiikkia, joka ylittäisi soitin- ja genrerajat. Kirjallisessa työssäni olen tarkastellut erityisesti harmonikan varhaisia myyntikanavia, harmonikkaa soittaneita varhaisia esiintyjiä sekä soittimen arvostukseen liittyviä seikkoja. Avainlähdeaineistona toimi Kansalliskirjaston ylläpitämä digitaalinen sanomalehtikirjasto, jonka kautta oli mahdollista koota monipuolisesti yhteen tietoja mm. soitinkauppiaista, soitinkorjaajista ja harmonikan rakentajista. Yhtenä tämän kirjallisen työn aiheena oli myös harmonikasta käytävä keskustelu keskellä kansanvalistuksen aikakautta. Avainhenkilönä tässä työssä oli saksalais-tanskalais-suomalainen harmonikkataiteilija Martin Paul (1843-1893), joka loi Suomessa vuosina 1879-1893 merkittävän uran sekä esiintyvänä taiteilijana että harmonikansoiton opettajana.
Keywords: Paul, Martin.; harmonikka; historia; populaarimusiikki; kansanmusiikki; kansanvalistus; MuTri